Calculation of Level Density Parameter of Nuclear Reaction Using Neural Network - Rizal Kurniadi; Yuda Satya Perkasa; Abdul Waris; Suwoto Suwoto (Institut Teknologi Bandung, 2009)
Level density parameter (LDP) calculation is dependent upon shell correction value, which usually is obtained by using Strutinsky method. The Strutinsky method is method that uses energy levels from certain potential as main input. Therefore for each mass number it strongly needs the energy levels calculation. The energy levels computation is time-consuming process; hence, the new application of computation technique is needed to reduce computation time. This paper explains the application of neural network in LDP calculation. Based on knowledge from box type and harmonic potentials, LDP is predicted by using arbitrary potential